Effectiveness of the Word Square Model in Improving Arabic Vocabulary Mastery of Madrasah Tsanawiyah Students / فعالية استخدام نموذج Word Square لترقية اكتساب مفردات اللغة العربية بالمدرسة المتوسطة الإسلامية الحكومية - Fauzi, Putri Awaliah; Zaenuri, Muhammad (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2024)
The mastery of Arabic vocabulary (Mufrodat) of students is still relatively low, this is evident when the learning process of students when asked about the meaning of a mufrodat is still many who do not know and do not answer. This can be influenced by several factors, therefore the researcher wants to conduct an experiment using the word square model when learning Arabic. The purpose of this study is to determine the effectiveness of using the word square model to improve the mastery of Arabic vocabulary in class VIII B MTs Negeri 2 Surakarta. This study uses a quantitative method of experiments with a one-group pre-test post-test design. The sample in this study is 31 students in class VIIIB. The data collection techniques are tests and documentation. The results of the study show that the word square model is declared effective in increasing vocabulary mastery. This can also be seen from the increase in student learning outcomes before and after the use of the word square model, namely the average score before using the word square 70 and the average after using the word square is 88. Based on the results of the hypothesis test using a paired sample t-test with a significant value result of 0.00 < 0.05. Therefore, Ho was accepted and H1 was rejected. Ho here is that there is an increase in vocabulary mastery in grade VIII B students of MTs Negeri 2 Surakarta.